Mutu Kimia Dan Organoleptik Nugget Ikan Tuna Dengan Penambahan Berbagai Kombinasi Tepung Wortel - If'all If'all; Minarny Gobel; Fahmi Fahmi; Irfan Pakaya (Lembaga Riset dan Pengabdian Kepada Masyarakat Universitas Djuanda Bogor, 2018)
The purpose of this research is to know and study various combination of carrot flour to chemical quality and organoleptic quality of tuna nugget. This study used Completely Randomized Design (RAL) with 4 treatments, and 4 replications. The research that will be done is as follows: R0 = 15% tapioca starch + 5% cornstarch + 0% carrot flour; R1 = 10% tapioca starch + 5% maize starch + 5% carrot flour; R2 = 5% tapioca starch + 5% maize flour + 10% carrot flour and R3 = 5% tapioca starch + 15% carrot starch. Each treatment was repeated four times, so there were 16 experimental units. To know the effect of the experiment, then the diversity test is done and if the result of the diversity test show the real effect, then continued with the test of the Least Significant Difference (LSD). The results showed that the addition of various carrot starch combinations had significant effect on protein content, crude fiber and tuna nugget fat but no significant effect on water content, b-carotene and organoleptic qualities of tuna nugget. a 10% tapioca starch combination, 5% cornstarch and 5% carrot flour give the highest levels of protein, coarse fiber, tuna nugget fat. Combination of 5% tapioca starch and 15% carrot flour gave the organoleptic qualities of tuna nuggets tend to be favored by panelists.